2005
DOI: 10.1088/1126-6708/2005/07/059
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on a class of renormalizable interpolating gauges

Abstract: A class of covariant gauges allowing one to interpolate between the Landau, the maximal Abelian, the linear covariant and the Curci-Ferrari gauges is discussed. Multiplicative renormalizability is proven to all orders by means of algebraic renormalization. All one-loop anomalous dimensions of the fields and gauge parameters are explicitly evaluated in the MS scheme.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…It is important to mention here that the diagonal condition do not follows from a extreme condition of any auxiliary functional and different choices could be taken for this sector. This is the case, for example, of the modified maximal Abelian gauge [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention here that the diagonal condition do not follows from a extreme condition of any auxiliary functional and different choices could be taken for this sector. This is the case, for example, of the modified maximal Abelian gauge [31].…”
Section: Discussionmentioning
confidence: 99%
“…One interesting feature of considering the interpolating gauge of Eq. (2) is that it can be extended to a six gauge parameter fixing which allows one to range over the linear covariant gauges, the Curci-Ferrari gauge and the MAG for various choices of the parameters, [22]. Indeed this generalized interpolating gauge has recently been analysed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed this generalized interpolating gauge has recently been analysed in Ref. [22] where it was shown that the one loop b-function is correctly independent of all six parameters and the usual anomalous dimensions emerge to be the known values when the parameters are fixed to those for the individual gauges.…”
Section: Discussionmentioning
confidence: 99%
“…Often, these families go under the name interpolating gauges. Examples include interpolating gauges between the Landau gauge and the Coulomb gauge [40,41], the Landau gauge and the maximally Abelian gauge [25,42,43], the linear covariant gauges, the Coulomb gauge and the maximally Abelian gauge [44,45], and the linear covariant gauges, the maximally Abelian gauge and the Curci-Ferrari gauge [46]. This article is structured as follows.…”
Section: Introductionmentioning
confidence: 99%